Improving Reading Comprehension by Using Summarizing Strategy: A Study on Eleventh Grade Students - Sahrawati Sahrawati; Konder Manurung; Agussatriana Agussatriana; Aminah Aminah (Universitas PGRI Sumatera Barat, 2025)
This research aimed at providing whether the use of summarizing strategy can improve reading comprehension of the eleventh-grade students of SMA Negeri 5 palu. This study employed a quasi-experimental research design with a sample of 49 students selected using a purposive sampling technique. The selected classes were class XI M2 and class XI M3. Furthermore, the research data were collected through a reading test administered twice as pre-test and post-test. The pre-test was given to the experimental and control groups before treatment while the post-test was given to both groups after the treatment. The mean score of the experimental group on the pre-test was 41.52 and the control group was 53.55. Then, the mean score of the post-test for the experimental group was 83.04 and the control group was 89.80. The data were analyzed statistically using the t-test formula with degrees of freedom (df) = Nx + Ny - 2 = 26 + 23 - 2 = 47. The findings show that the t counted value is 2.342 while the t-table value is 2.011. This means that the t counted is higher than the t-table. Therefore, the research hypothesis is accepted. This finding answered the question from the problem formulation that the use of summarizing strategy can improve the reading comprehension of the eleventh-grade students of SMA Negeri 5 palu. The implication of this finding is that teachers need to use summarizing strategy in teaching reading comprehension designed to make students be able to express ideas, perform better reading, and develop their creative thinking in class. Keywords: Reading Comprehension, Summarizing Strategy.